PEMILIHAN PORTOFOLIO DENGAN MENGGUNAKAN PEMODELAN MIXTURE OF MIXTURE - , MIDIAN RAJAGUKGUK ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The development of technologi, information and communication is spread out and indirectly has colored creation advances global investment instrument in the capital markets. A wide variety of instruments have been traded publicy and is able to provide facilities and opportunities to investors sufficient flexibility to increase investment ways. Benefits could be very large and fast by investing as simultaneous or concurrent with the right. This will force investors to be aware of the need for risk management decision making can enliven. The method is quite old and popular as well as simple statistical calculation of risk in the portfolio is invested in Value at Risk (VaR). This method provides a way of calculating the value of the minimum loss over the selected portfolio at a certain confidence level. By dividing into several segments based on time and world economic activity and then do a modeling portfolio from the several stocks (BBNI.JK, BNGK.JK, BMRI.JK, AALI.JK, gold) using a mixture of mixture density will represents in explaining patterns return and simultaneously use the result to calculate the amount of risk to be accepted.